Anticancer Activity of Sulforaphane: The Epigenetic Mechanisms and the Nrf2 Signaling Pathway. (6th June 2018) - Su, Xuling; Jiang, Xin; Meng, Lingbin; Dong, Xiaoming; Shen, Yanjun; Xin, Ying
Abstract : Sulforaphane (SFN), a compound derived from cruciferous vegetables that has been shown to be safe and nontoxic, with minimal/no side effects, has been extensively studied due to its numerous bioactivities, such as anticancer and antioxidant activities. SFN exerts its anticancer effects by modulating key signaling pathways and genes involved in the induction of apoptosis, cell cycle arrest, and inhibition of angiogenesis. SFN also upregulates a series of cytoprotective genes by activating nuclear factor erythroid-2- (NF-E2-) related factor 2 (Nrf2), a critical transcription factor activated in response to oxidative stress; Nrf2 activation is also involved in the cancer-preventive effects of SFN. Accumulating evidence supports that epigenetic modification is an important factor in carcinogenesis and cancer progression, as epigenetic alterations often contribute to the inhibition of tumor-suppressor genes and the activation of oncogenes, which enables cells to acquire cancer-promoting properties. Studies on the mechanisms underlying the anticancer effects of SFN have shown that SFN can reverse such epigenetic alterations in cancers by targeting DNA methyltransferases (DNMTs), histone deacetyltransferases (HDACs), and noncoding RNAs. Therefore, in this review, we will discuss the anticancer activities of SFN and its mechanisms, with a particular emphasis on epigenetic modifications, including epigenetic reactivation of Nrf2.